Variation with Ni and Mn of the structural stability, magnetic properties and Kovar effect in Fe–Ni–Co based alloys - Kai Wang; Zhaolin Wang; Kaichao Zhang; Chao Lv; Huilong Hou; Xinqing Zhao (Journal of Materials Research and Technology)
As a typical commercial Kovar alloy, the Fe–Ni–Co based alloy with nominal ∼29 wt% Ni, ∼17 wt% Co, and minor Mn and Si has found abroad applications in electronic and optoelectronics fields because of its analogous thermal expansion coefficient to borosilicate glass as well as high Curie temperature. Owing to the limited structural stability in cryogenic environments, the alloy is suggested to use above 193 K to avoid the failure by austenite to martensite transformation. In this work, the structural stability, magnetic properties, and Kovar effect of Fe54-xNi29+xCo17 (x = 0, 3, 6) and Fe54-xNi29Co17Mnx (x = 0, 1, 2, 4) alloys were systematically investigated, attempting to extend the application of Fe–Ni–Co based Kovar alloys in extremely low-temperature environments. The results achieved in the study indicated that the martensitic transformations could be completely suppressed in Fe54-xNi29+xCo17 (x = 3, 6) and Fe54-xNi29Co17Mnx (x = 2, 4) alloys at 77 K. The structural stability, Curie temperature, and CTEs increase with increasing Ni content in Fe54-xNi29+xCo17 (x = 0, 3, 6) alloys. The increase of Mn in Fe54-xNi29Co17Mnx (x = 0, 1, 2, 4) alloys gave rise to the enhancement of structural stability, reduction of Curie temperature, and sluggish increment of CTE with invariant CTE value in the temperature range from 550 K to 200 K. By comparison with Ni, the incorporation of Mn has a lesser effect on the CTE of Fe–Ni–Co based Kovar alloys, bringing benefit to the application in hermetic seals between metals and glass.